Turbulence and dispersion in the planetary boundary layer - Tampieri, Francesco (Springer, 2016)
This book offers a comprehensive review of our current understanding of the planetary boundary layer, particularly the turbulent exchanges of momentum, heat and passive scalars between the surface of the Earth and the atmosphere. It presents and discusses the observations and the theory of the turbulent boundary layer, both for homogeneous and more realistic heterogeneous surface conditions, as well as the dispersion of tracers. Lastly it addresses the main problems arising due to turbulence in weather, climate and atmospheric composition numerical models. Written for postgraduate and advanced undergraduate-level students and atmospheric researchers, it is also of interest to anyone wanting to understand the findings and obtain an update on problems that have yet to be solved.
Keywords: Boundary layer (Meteorology); Atmospheric turbulence.; elektronické knihy; electronic books